KARAKTERISTIK HARD CANDY MINYAK ATSIRI DAUN KEMANGI (Ocimum basilicum L.) DENGAN PENAMBAHAN EKSTRAK DAUN KERSEN (Muntingia calabura L.) - Syafri Dwiananta; Bara Yudhistira; Rohula Utami (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
Basil leaf essential oil hard candy with the addition of cherry leaf extract is an innovation in the food sector in an effort to develop functional food products by adding antioxidant activity through natural ingredients that are easily found. Basil is a plant that is often used as a producer of essential oils. The addition of basil to dishes creates a distinctive aroma that enhances the taste buds and results in longer cooking. Cherry leaves contain various compounds such as flavonoids, tannins, triterpene, sanponins and polyphonols which have antioxidant activity.Flavonoids themselves also function as antihypertensive, antimicrobial, anti-inflammatory and can treat liver dysfunction. This study aims to determine the best formulation of hard candy basil essential oil with the addition of cherry leaf extract based on chemical, physical, and sensory analysis. The experimental design in this study was a completely randomized design (CRD). In this study there were 5 formulas, namely, Formula 1 (80% addition of cherry leaf extract per volume of material), Formula 2 (60% addition of cherry leaf extract per volume of material), Formula 3 (50% addition of cherry leaf extract per volume of material), Formula 4 (40% addition of cherry leaf extract per volume of material), Formula 5 (20% addition of cherry leaf extract per volume of material). Data analysis in this study used the One Way ANOVA method, with the DMRT further test at the 95% significance level. Based on the research results obtained Formula 5 as the best formula with a water content of 1.844%, ash content of 2.141%, reducing sugar content of 18.338%, water activity of 0.525, pH of 6.850, and antioxidant activity of 6.643%, color 82.594 0Hue, hardness of 477.660 N, and cohesiveness. 0.120 N, with the overall panelist acceptance rate being somewhat favorable